Seroprevalence of IgG antibodies against pertussis toxin in the Chinese population: A systematic review and meta-analysis - Yao Zhu; Wanting Zhang; Jie Hu; Shuying Luo; Yang Zhou; Xuewen Tang; Rui Yan; Xuan Deng; Hanqing He (Taylor & Francis Group, 2024)
ABSTRACTPertussis is a vaccine-preventable infectious disease; however, data on pertussis antibody levels in a nationwide population are still limited in China. We aimed to pool the seropositivity rates of IgG antibodies against pertussis toxin (PT-IgG) across the country. We systematically searched PubMed, Web of Science, Embase, and the China National Knowledge Infrastructure Database for studies published between January 1, 2010, and June 30, 2023. Studies reporting the seroprevalence of PT-IgG among a healthy Chinese population were included. Pooled estimates were obtained using random-effects meta-analyzes. The meta-analysis included 39 studies (47,778 participants) reporting anti-PT IgG seropositivity rates. The pooled rate for all ages was 7.06% (95% CI, 5.50%-9.07%). Subgroup analyzes showed rates ranging from 6.36% to 12.50% across different age groups. This meta-analysis indicated a low anti-PT IgG seropositivity rate in the Chinese population, particularly among school-aged children and young adults. This finding underscores the urgent need to refine immunization strategies.